Contribution to the knowledge of the cavernicolous beetle genus Aspidaphaenops Uéno from Guizhou (Coleoptera: Carabidae: Trechinae) - Tian, Mingyi; Huang, Sunbin (Zootaxa, 2018)
The hypogean ground beetle genus Aspidaphaenops Uéno, 2006 is reviewed. Some new information of A. reflexus Uéno, 2006 is provided, including the male genital characteristics as well as a new locality. Two new species are described and illustrated from southwestern Guizhou Province, southwest China: A. xiongda n. sp. (Guizhou: Anlong: Fengyan Dong), A. dudou n. sp. (Guizhou: Xingyi: Xiaozi Dong). A key to all Aspidaphaenops species is also provided.